State of Implementation of Senior High School Program: An Explanatory Analysis of Administrative and Instructional Practices - Ramos, Rigette Ryan (JPAIR Multidisciplinary Research, 2018)
This study dealt to explore the administrative and instructional practices associated with the implementation of the Senior High School Program in the Division of Pampanga in aid of policy recommendation. It described how administrators and teachers assess the level of readiness of schools; administrative and instructional practices that are utilized; common problems and their coping measures; significant insights and observations and the policy recommendation that may be proposed. The study made use of the descriptive evaluation method utilizing the Mixed Method Explanatory Sequential Design in data analyzing, for the purposes of breadth and depth of understanding and corroboration. Based on the results, the Division of Pampanga has the readiness to offer the program. Administrators have been pursuing their administrative and instructional functions. There are issues hindering implementation that need to be addressed. Administrators and teachers are doing their very best to find solutions to their encountered problems. The following are the recommendations; Administrators may study the possibility of strategically aligning the local school board funds. Administrators may continue the training, and supporting teachers to do action researches. Concerned schools may revisit the different ways and means on how the problems can be solved.
Keywords: Education; Senior High School; Administrative and Instructional Practices; mixed method research design; Philippines